Implementasi Pembelajaran Tahfidzul Qur’an Berbasis Masjid - Muhammad Arifin; Rekza Rekza (STAI Al-Hamidiyah Jakarta, 2024)
This study aimed to examine the implementation of the tahfidzul Qur'an learning process at Ma'had Al-Askar Sawangan, Depok, identify the supporting and inhibiting factors in this process, and evaluate the outcomes of the tahfidzul Qur'an learning process at Ma'had Al-Askar Sawangan, Depok. The research method employed was a descriptive-qualitative approach. Data were collected through interviews, observation, and documentation. The data analysis utilized an interactive analysis model proposed by Miles and Huberman, commonly referred to as the flow model analysis. The results revealed the following: 1) The tahfidzul Qur’an learning process at Ma'had Al-Askar is reflected in the daily activities that students are required to adhere to, running from Monday to Friday. 2) Supporting factors for the tahfidzul Qur’an learning process include a comfortable and conducive learning environment, a democratic and non-authoritarian leadership style of the caregivers/ustadz, and harmonious relationships between students and caregivers as well as among fellow students. The inhibiting factors are primarily internal, originating from the students themselves as memorizers. These internal factors include laziness, drowsiness, homesickness, lack of discipline, and other personal challenges. 3) The outcomes of the Tahfidzul Qur’an learning process at Ma'had Al-Askar demonstrate that students not only succeeded in memorizing the Qur’an but also acquired additional skills, such as leading congregational prayers, performing the adhan and iqamah, and interacting effectively with the community.